Nonlinear response and driving mechanisms of ecological restoration project effectiveness to drought - Xin Liu; Qi Wang; Xiaoyu Zhu; Yujun Zhang (Ecological Indicators)
Ecological Restoration Projects (ERP) are hypersensitive to drought stress. Nevertheless, a scarcity of cognition remains regarding how drought impacts ERP effectiveness and how socio-ecological factors drive this relationship. This study utilized a constraint line to explore the nonlinear response relationship between ERP effectiveness and drought in the Agro-pastoral Transitional Zone of Northern China (APTZNC) located in the arid and semi-arid regions. By identifying thresholds and employing PLS-SEM models, the study reveals the mechanisms by which socio-ecological factors influence the relationship between the two. The results showed that: (1) drought has a significant inverted ‘U’ shaped nonlinear effect on ERP effectiveness, with a threshold of 0.3673, dividing the arid region and moderately arid region. (2) The influence of socio-ecological factors on the relationship between ERP effectiveness and drought varies significantly across different arid environments. The number and intensity of impact pathways are much more pronounced in moderately arid regions than in arid regions, leading to greater direct impacts (−0.891, −0.203) and indirect impact benefits (−0.079, −0.01). (3) Further identification of priority areas for restoration and management based on hot and cold spots, and provided governance insights in three aspects: zoning, governance pathways, and priority management areas. Our study highlights the importance of considering zoning differences caused by threshold effects when implementing and managing ERP. The research offers a theoretical foundation for ecological restoration and sustainable development of the APTZNC and scientific guidance for implementing ecological restoration practices in other regions experiencing drought stress globally.